Analisis Perbandingan Motivasi dan Etos Kerja Pedagang Rantau Dengan Pedagang Lokal (Studi Kasus Kec. Selong Kabupaten Lombok Timur) - Safi'i, Muh. Safi'i; Nurudin, Ayuddin (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2024)
Motivation is a factor that can encourage individuals to do certain activities. While Work Ethic emphasizes that creative work is one source of happiness and achievement. Hard work is considered a virtue so that a trader who does his job with hard work and high spirits is likely to progress in his life, conversely if someone does not work hard in completing his work, his life is likely to fail. This study aims to determine the motivation and work ethic and analyze the differences between migrant traders and local traders. The method used in this study is a descriptive qualitative approach. The data in this study were obtained through observation, interviews and data documentation, then analyzed by reducing the data, presenting and drawing conclusions. The conclusions of this study are as follows: 1.) The main motivation of migrant traders and local traders in working is to meet the needs of themselves and their families. In addition to family motives, the motivation of migrant and local traders in running their businesses is to improve the level of family welfare and raise their standard of living. This can be seen from how to respond to the high and low levels of the number of consumers who choose to shop at their stalls and the level of income they earn. 2.) A good work ethic among fellow traders can provide a positive influence on a healthy work environment so that business competition between traders is not too obvious. In relation to the work ethic between local traders and migrant traders in Pancor Village, a good work ethic can provide comfort so that it can affect the level of productivity.